Strategi Komunikasi Visual Kemasan Kain Gambo Khas Musi Banyuasin - Ahmad Ridho Amirullah; Husni Mubarat; Yosef Yulius (VisArt: Jurnal Seni Rupa dan Design, 2025)
Gambo cloth is one of the unique cultural heritages from Musi Banyuasin, South Sumatra, which holds high historical, cultural, and aesthetic value. Despite its exceptional quality and uniqueness, the marketing of gambo cloth still faces various challenges, one of which is packaging that is less attractive and not aligned with the development of the modern market. Ineffective packaging can reduce consumer appeal and influence perceptions of product quality. Therefore, appropriate packaging is very important to introduce gambo cloth more widely and increase its marketability. This design aims to create gambo cloth packaging that not only functions as product protection but also serves as an effective promotional tool to showcase the culture and beauty of gambo cloth. The outcome of this design is expected to contribute to the preservation of gambo cloth culture, as well as to increase understanding and appreciation of this product. With proper packaging, gambo cloth can be more easily introduced to the public. In addition, it is expected that this packaging design will also boost purchase interest, create brand awareness, and support the sustainability of the gambo cloth craft industry in Musi Banyuasin